Sustainable and Green Architecture Industrial Technology: Challenges and Future Directions - Aryanti, Dwi; Abdullah Ali; Usman, Ridwan; Sri Mumpuni Ngesti Rahaju; Ghazali, Ihwan (The Indonesian Institute of Science and Technology Research, 2024)
Sustainable design plays a pivotal role in addressing environmental and social concerns within the field of architecture. This concept involves the integration of sustainability principles throughout the architectural design process, encompassing social sustainability, sustainable materials and construction methods, and sustainability assessment. Architects can create structures that demonstrate environmental consciousness, optimize resource use, promote social inclusivity, and preserve cultural significance by incorporating these fundamental principles. However, the successful implementation of sustainable architecture faces several challenges. These challenges include limited awareness among professionals, resistance to change in the industry, complexities in integrating sustainability, and budget constraints. Overcoming these hurdles necessitates comprehensive education, government support, adherence to regulations, technology utilization, and economic incentives to encourage the adoption of sustainable design techniques. Despite these challenges, the field of sustainable architecture holds significant potential for further advancement. Opportunities for exploration include integrating emerging technologies like artificial intelligence and machine learning, applying sustainable architectural principles in urban planning, advancing sustainable materials and construction methods, considering social sustainability, and developing comprehensive frameworks for holistic sustainability assessment. By advancing knowledge and innovation in these areas, sustainable architecture can contribute substantially to creating a more sustainable built environment. Architectural professionals, through collaboration, interdisciplinary approaches, and a commitment to long-term sustainability, have the potential to play a crucial role in shaping a sustainable future for urban areas and communities.